Back on track: exploring how a further education college re-motivates learners to re-sit previously failed qualifications at GCSE. Issue 3 (2nd July 2016) - Anderson, Nadia; Peart, Sheine
Abstract: Underachievement at GCSE level has significant effects on an individual's life chances. Each year, around half of 16-year-olds leave school without having achieved a full level-2 qualification (five GCSEs at A*–C including English and maths). Many of these students enrol on a programme of study at local further education (FE) colleges. Recent Coalition government reforms, including raising the participation age and compulsory English and Maths study up to aged 19, have reaffirmed FE as an agent to improve students' life chances and act as a catalyst to reduce youth unemployment. Further education colleges provide a 'second chance' for learners who have failed at school. This research shows that students who have previously attended low-performing schools, arrive with low motivation, low levels of self-efficacy and a negative perception of education. Focus-group discussions with GCSE resit students studying at an FE college, followed by individual interviews, revealed that school experience of unprofessional teacher-pupil relationships, a lack of discipline, inconsistently applied sanctions, a lack of academic support and prevalent low-level disruption all contributed to demotivating the students. The data revealed that students' experience at college was significantly different when compared to secondary school. Professional and supportive relationships with teachers, classroom management strategies leading to learner ownership and autonomy, consistently applied behaviour management practices and visible senior leadership enabled learners to re-engage in education at FE and successfully re-sit their GCSE examinations.